2018
DOI: 10.1039/c8cp02734j
|View full text |Cite
|
Sign up to set email alerts
|

A facile synthesis of segmented silver nanowires and enhancement of the performance of polymer solar cells

Abstract: In this work, segmented silver nanowires (AgNWs) with an average diameter of 60 nm have been successfully synthesized by a typical polyol method without any templates and seeds. The synthesized segmented AgNWs were strongly dependent on the reaction temperature and time. It was found from high-resolution transmission electron microscopy and selected area electron diffraction measurements that the connection node of segmented AgNWs was in the form of a twinned crystal. We speculated that these segmented AgNWs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…The prepared PV cell using MP-AgNW-based TCE showed a PCE of 3.18%, which was 28% higher than the one using SP-AgNW-based TCE. A similar study has also been reported by Wei et al [105].…”
Section: Building Applications Using Metallic Nwssupporting
confidence: 89%
“…The prepared PV cell using MP-AgNW-based TCE showed a PCE of 3.18%, which was 28% higher than the one using SP-AgNW-based TCE. A similar study has also been reported by Wei et al [105].…”
Section: Building Applications Using Metallic Nwssupporting
confidence: 89%
“…NPs also assist in the charge transport at the interface. NPs are synthesized by different methods such as chemical reduction, the polyol method, and ultrasonochemical synthesis [ 289 ]. Hao et al reported mixed AuNPs (rod, bone-like, cube and spheres shape) doped in PEDOT:PSS HTLs in OSCs based on PTB7:PC 71 BM [ 290 ].…”
Section: Hole-transporting Materials As Htls In Oscsmentioning
confidence: 99%
“…Better device performances were obtained with NPs because of the surface-plasmon effect (at the visible region for AuNPs) that increased the photoabsorption length and the trapping of scattering and incident light. Segmented silver nanowires (AgNWs) were incorporated in PEDOT:PSS HTLs in OSCs with configuration ITO/PEDOT:PSS:AgNWs/P3HT:PC 61 BM/ZnO/Al [ 289 ]. These OSCs exhibited enhanced device performance with a PCE of 3.3%, increased J sc and FF due to LSPR, and optical-scattering properties from the AgNWs.…”
Section: Hole-transporting Materials As Htls In Oscsmentioning
confidence: 99%
“…In this process, TBADCB, an organic halide with high thermal stability, acted as a soft template and ionic halogen salt containing an ammonium cation and a BrCl 2 anion [131]. Wei et al introduced a facile polyol synthesis of segmented AgNWs through end-to-end self-connection of twinned crystals of neighboring rods or wires with an average dimeter of 66 nm [132]. Tang et al studied a novel modified AgNW synthesis process to control and reduce the high activity defects of synthesized AgNWs through an etching process in which a locally uneven ligand distribution is required to provide more ligand molecules in the nucleation step and less in the growth step.…”
Section: Effect Of the Mixing Type And Rate In The Polyol Synthesismentioning
confidence: 99%
“…Wei et al explained the reaction mechanism behind the formation of segmented AgNWs including the initial steps of formation of single nanowires with assistance of a salt mediator and a capping agent. They attributed the formation of segmented wires to the higher potential energy of the end atoms causing them to diffuse to the sides or attach end to end to reduce the surface chemical potential [132]. Tang et al described a detailed reaction mechanism in the polyol process involving an etching effect.…”
Section: Reaction Mechanism Of Agnw Polyol Synthesismentioning
confidence: 99%